2017
DOI: 10.1016/j.tjog.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Single incision anterior apical mesh and sacrospinous ligament fixation in pelvic prolapse surgery at 36 months follow-up

Abstract: SIM A has better 3 years objective and subjective cure rate than SSF in the anterior and/or apical compartment prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
5
8
0
Order By: Relevance
“…To the best of our knowledge, our study is the first focusing on surgical management of patients with symptomatic advanced POP with the modified Surelift system, and has demonstrated good 1-year objective and subjective outcomes. Anatomic correction of anterior and apical prolapse was 100%, which compares favorably with results from previous similarly conducted studies using Elevate-A and Uphold [4,5]. The subjective cure rate at 1 year was 92.8%.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the first focusing on surgical management of patients with symptomatic advanced POP with the modified Surelift system, and has demonstrated good 1-year objective and subjective outcomes. Anatomic correction of anterior and apical prolapse was 100%, which compares favorably with results from previous similarly conducted studies using Elevate-A and Uphold [4,5]. The subjective cure rate at 1 year was 92.8%.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study with 52-month follow-up showed an objective cure rate of 94.4% for a transvaginal mesh (TVM) used for advanced vaginal cuff eversion [3]. The Elevate-A system (Elevate Anterior and Apical Prolapse Repair System, American Medical Systems, Minnetonka, MN), a single-incision mesh system for anterior and apical prolapse repair, had showed 3-year objective cure rates of 96.6% and 98.3% in the anterior and apical compartments, respectively [4]. Similarly, the Uphold Lite vaginal mesh system (Boston Scientific, Marlborough, MA) with proximal mesh placement on the bilateral sacrospinous ligaments had promising 1-year 95.5% and 94.3% objective and subjective cure rates, respectively, for patients with symptomatic anterior or apical prolapse stage III or IV [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An 11-year population-based nationwide descriptive study showed a trend of uterine suspension with uterine preservation during the latter years, [19] and the uterus preservation is always considered when there is no pathological finding of uterus. [20] In 2014, this minimally invasive procedure of UPHOLD LITE Vaginal Support System with the Capio SLIM Suture Capturing Device (Boston Scientific, Marlborough, MA, USA) has been used in our hospital. More than 500 patients have been treated with this procedure so far.…”
Section: Discussionmentioning
confidence: 99%
“…SSF was fixed on the right unilateral side via the posterior approach 12 . No additional support was done for TVM that provided anterior and apical support such as Prolift anterior and posterior (Prolift T) 13 , Elevate Anterior/Apical (Elevate A) 14 , and Uphold. Concomitant MUS (Transobturator tape) was offered to patients with higher score in question #3 (Urine leak related to physical activity, coughing or sneezing) than #2 (Urine leakage related to the feeling of urgency) on UDI-6.…”
Section: Methodsmentioning
confidence: 99%